2009
DOI: 10.1111/j.1464-5491.2009.02727.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of grape seed extract in Type 2 diabetic subjects at high cardiovascular risk: a double blind randomized placebo controlled trial examining metabolic markers, vascular tone, inflammation, oxidative stress and insulin sensitivity

Abstract: GSE significantly improved markers of inflammation and glycaemia and a sole marker of oxidative stress in obese Type 2 diabetic subjects at high risk of cardiovascular events over a 4-week period, which suggests it may have a therapeutic role in decreasing cardiovascular risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
180
2
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(194 citation statements)
references
References 33 publications
10
180
2
2
Order By: Relevance
“…These results suggest that daily consumption of GPE might prevent hyperglycemia caused by high fat diet. Similar evidence was obtained by Laight et al [29] who reported that consumption of grape seed extract for 4 weeks significantly improved markers of inflammation and glycaemia in obese Type 2 diabetic subjects with 32 patients involved in a double blind randomized placebo controlled trial.…”
Section: Discussionsupporting
confidence: 71%
“…These results suggest that daily consumption of GPE might prevent hyperglycemia caused by high fat diet. Similar evidence was obtained by Laight et al [29] who reported that consumption of grape seed extract for 4 weeks significantly improved markers of inflammation and glycaemia in obese Type 2 diabetic subjects with 32 patients involved in a double blind randomized placebo controlled trial.…”
Section: Discussionsupporting
confidence: 71%
“…The most frequent observation was an increase of the expression and activity of GPX and SOD and of the levels of GSH [21,22,23]. Only two in vitro studies reported a decrease of GSH [24,25]. In the present study, we were unable to show a significant effect of RES on the antioxidant enzymes.…”
Section: Discussioncontrasting
confidence: 51%
“…Results of clinical studies testing the effect of GSEs on the total antioxidant status are controversial. Two clinical studies that studied the effect of a GSE [17,18] on TAP with the same method as in the present study did not show any significant effect on the antioxidant status. Two other clinical studies that used the total antioxidant capacity [19] or the oxygen radical absorbance capacity [20] methods showed significant increases of antioxidant capacity after GSE (Leucoselect®) or French maritime pine bark extract (Pycnogenol) intake, respectively.…”
Section: Discussionmentioning
confidence: 68%
“…Resveratrol, quercetin, catechins, and anthocyanins have been shown to inhibit hyperglycemia, improve beta-cell function, and protect against beta-cell loss. In obese Type 2 diabetic subjects, GSE significantly improved inflammation and glycemic status and decreased oxidative stress and total cholesterol levels (Kar et al 2009). Analyses of epidemiological studies concluded that moderate regular alcohol consumption is associated with an ~30% reduced risk of type 2 diabetes (Howard et al 2004, Koppes et al 2005, indicating that the benefits afforded by the alcohol and polyphenol contents of red wine are probably additive.…”
Section: Type 2 Diabetesmentioning
confidence: 99%